Clinlcopathological Study of Ovarian Cancer: A Multi Centered Study - Deeba, Farzana; Alam, ABM Muksudul; Banu, Jesmin (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Ovarian cancer is one of the leading causes of morbidity and mortality. Objectives: The purpose of the present study was to find out clinic-demographic and histopathological variants of ovarian cancer. Methodology: This cross-sectional study was conducted in the Department of Obstetrics and Gynaecology at four largest tertiary care Hospitals in Dhaka city from January 2008 to December 2009. Clinically diagnosed and histopathologically confirmed ovarian cancer patients were included in this study. Result: Histopathological confirmed 28 patients of ovarian cancer were enrolled in this study. The mean age (±SD) was 40.6 (±12.5) years (Range 13 to 63 years). Lower abdominal lump (71.4%) was the most common symptoms. Family history (14.0%) and multiparty (53.0%) were also associated with ovarian cancer. Among 28 malignant tumors cases serious cyst adenocarcinoma (57.1%) was the most common followed by mucinous cyst adenocarcinoma (17.9%), dysgerminoma (7.1%), adenocarcinoma of ovary (7.1%), ovarian choriocarcinoma (3.6%) and endometriod adeno carcinoma (3.6%). High serum CA125 was found in 78.0% cases. Conclusion: Lower abdominal lump, multiparity and positive family history are the common clinical findings of ovarian cancer. Both serous and mucinous cyst adenocarcinoma are the common varient of ovarian cancer found in this study. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16196 J Shaheed Suhrawardy Med Coll, 2013;5(1):3-6